Parâmetros genéticos para características relacionadas a resistência a parasitas e eficiência reprodutiva de caprinos de corte criados sob condições de pastagens subtropicais úmidas do sudeste dos Estados Unidos da América - Silva, Michelle Santos da (2018)
The objective of this study was to evaluate genetically the performance of meat goats in relation to their resistance to gastrointestinal parasites and their reproductive efficiency in the Southeastern United States. These animals are part of a genetic evaluation program for meat goats, Meat Goat Genetic Evaluation System (MGGES), in partnership with Embrapa Goats and Sheep, through the Breeding Program for Meat Goats and Sheep (GENECOC), comprising the Boer, Kiko, Spanish, Myotonic and Savannah breeds and their crossing. The focus of the program is selected genetic groups and higher animals for meat production. Because it is a humid region and animals are managed on pasture, one of the major challenges of the exploration is the gastrointestinal parasitism, so the selection of resistant animals is fundamental. One of the most efficient methods in this selection is the use of the Gordon and Withlock technique for counting eggs per gram of faeces (OPG). Initially, the previously transformed OPG trait was evaluated in the goat does at three different times: in the mating (OPGC), in the kidding (OPGP) and in the weaning of the offspring (OPGD), together with the traits of reproductive efficiency: number of kids born (NCN) and number of kids weaned (NCD). Linear models for all OPG traits and threshold for NCN and NCD traits were performed. In the second moment, only the OPGC, OPGP and OPGD traits were analyzed through the repeatability and random regression models. For both, Bayesian inference was performed via Gibbs sampling with chains of 2,000,000 iterations and sampling discard of the first 5,000 chains in a sampling period every 50 iterations. The deviance information criteria (DIC) was used to evaluate the best transformation of OPG data. The 39,900 effective iteration chains were sufficient to adequately estimate the variances and covariates in the analysis for the characteristics. The genetic parameters for OPG differed with the moment of the measurement of this characteristic, being expected a better response to the selection for resistance to the gastrointestinal parasitism when the selection for OPG is practiced at the time of the birth of the matrices. The NCN and NCD characteristics should be assessed as threshold because they allow higher estimates of heritability. In the random regression model the heritability and repeatability of the OPG were estimated with low magnitude and small potential for change. Even so, it was observed that the best time to perform selection for resistance to parasitoses by counting the OPG of the matrices would be for the younger animals at the time of their first birth. The genetic correlations between OPG measurements were higher at ages closer to each other, with a tendency to be negative between the extreme ages.